Nutrient retention in popular dishes based on Google Trends data in Hatay cuisine - Öney, Başak; Yılmaz, Solmaz Ece; Güçlü, Duygu (ARAN Ediciones S.L, 2023)
Introduction: Hatay cuisine has an important place in Turkey and world cuisine. It consists of meat dishes, stuffed vegetables, vegetable dishes, jams, pickles, pilafs, soups, appetizers and salads, herbs collected from nature, desserts, pastries, dairy products and dry foods. The culinary processes differing in cultures alter nutrient value of foods. Food preparation and processing operations affect contents and bioavailability of micronutrients in traditional dishes. Several studies have been carried out to investigate the influence of traditional food preparation and processing methods in vitamins and minerals. In this study, nutrient retention in popular dishes of Hatay cuisine was analyzed. Material and methods: Google Trends is an open access tool that allows to determine the popularity of search terms. In the current study, the most common dishes searched in the last 12 months by individiuals living in Hatay province were selected. Şıhılmahşi, tepsi kebabı, tuzlu yoğurt çorbası, humus and künefe were the most searched on the web. We used the Nutrient Retention Factor Table of the United States Department of Agriculture (USDA), and the nutrient content of the Turkish traditional dishes described above was calculated after cooking of Hatay cuisine. Results: the highest loss of micronutrients has been found in vitamin B6, folate, vitamin B12 and thiamine. In şıhılmahşi, the highest loss was in folate, with 40 %. In tepsi kebabı, the highest loss appeared in vitamin B6, with 50 %. In tuzlu yoğurt soup, 70 % loss of B12 was reported. In humus, the highest loss was in folate at the level of 40 %. In künefe, the most loss occurred in folate with 30 %. Conclusion: specific cooking, preparation and preservation practices of traditional dishes that are compatible with local experience can be encouraged as an alternative or adjunct to other methods of increasing the availability of micronutrients in foods.

Introducción: la cocina Hatay tiene un lugar importante en Turquía y en la cocina mundial. Se compone de platos de carne, verduras rellenas, platos de verduras, mermeladas, encurtidos, pilafs, sopas, aperitivos y ensaladas, hierbas recolectadas de la naturaleza, postres, repostería, productos lácteos y alimentos secos. Los procesos culinarios que difieren en las culturas alteran el valor nutritivo de los alimentos. Las operaciones de preparación y procesamiento de los alimentos afectan el contenido y la biodisponibilidad de los micronutrientes en los platos tradicionales. Se han llevado a cabo varios estudios para investigar la influencia de los métodos tradicionales de preparación y procesamiento de alimentos en las vitaminas y los minerales. En este estudio se analizó la retención de nutrientes en platos populares de la cocina Hatay. Material y métodos: Google Trends es una herramienta de libre acceso que permite determinar la popularidad de los términos de búsqueda. En el estudio actual, se seleccionaron los platos más comunes buscados en los últimos 12 meses por personas que viven en la provincia de Hatay. Şıhilmehşi, kebab en bandeja, sopa de yogur salada, hummus y künefe fueron los más buscados en la web. Usamos la tabla de factores de retención de nutrientes del Departamento de Agricultura de Estados Unidos (USDA, por sus siglas en inglés) y el contenido de nutrientes de los platos tradicionales turcos descritos anteriormente se calculó después de cocinar la cocina Hatay. Resultados: las mayores pérdidas de micronutrientes se han encontrado en vitamina B6, folato, vitamina B12 y tiamina. En Şıhilmehşi, la pérdida más alta fue de folato, con un 40 %. En el kebab en bandeja la mayor pérdida se presentó en vitamina B6, con un 50 %. En la sopa de yogur salada, se informó una pérdida del 70 % de B12. En hummus, la mayor pérdida fue en folato, a un nivel del 40 %. En künefe, la mayor pérdida se presentó en folato, con un 30 %. Conclusión: se pueden fomentar prácticas específicas de cocción, preparación y conservación de platos tradicionales que sean compatibles con la experiencia local como alternativa o complemento de otros métodos para aumentar la disponibilidad de micronutrientes en los alimentos.
Retención de nutrientes en platos populares según datos de Google Trends en cocina Hatay
Keywords: Hatay Cuisine; Cooking Methods; Nutrient Retention; Micronutrients; Traditional Dishes; Cocina Hatay; Métodos de Cocina; Retención de Nutrientes; Micronutrientes; Platos Tradicionales